(untitled) (Journal of Laboratory Animal Science, 2025)
Chronic inflammatory muscle pain represents a significant clinical challenge with limited therapeutic options. This study investigates the modulatory effects of zingerone, a bioactive compound derived from ginger (Zingiber officinale), on prostaglandin E2 (PGE2) signaling pathways in the chronic myalgia model. Using an integrated approach combining in vivo, in vitro, and in silico analyses, we demonstrate that zingerone significantly attenuates inflammatory muscle pain. In vivo studies using carrageenan-induced muscle inflammation in rats showed a substantial reduction in pain behaviors and inflammatory markers following zingerone administration (20-40 mg/kg). In vitro experiments revealed zinge rone’s inhibitory effects on PGE2 production in a dose-dependent manner. Molecular docking simulations identified key binding interactions between zingerone and the PGE2, cyclooxygenase-2 (COX-2) enzyme active site, with a predicted binding affinity of -4.8 and -6.4 kcal/mol, respectively. Zingerone treatment significantly modulated the PGE2/COX-2 signaling pathway, further supporting its anti-inflammatory properties. These findings suggest that zingerone represents a promising natural therapeutic agent for chronic inflammatory muscle pain conditions through its targeted inhibition of PGE2-mediated inflammatory cascades.